Arterial Responses to Acute Low-Level Ergot Exposure in Hereford Cows - Cowan, Vanessa Elizabeth; Neumann, Alex; McKinnon, John; Blakley, Barry Raymond; Grusie, Taylor Jayne; Singh, Jaswant (Frontiers in Veterinary Science, 2018)
Ergot alkaloids are toxic secondary metabolites produced by the fungus Claviceps purpurea that contaminate cereal grains. Current Canadian standards allow 2 to 3 parts per million of ergot alkaloids in animal feed. The purpose of this study was to determine whether hemodynamic parameters were altered when beef cows were fed permissible levels of ergot alkaloids (i.e., <3 ppm) on a short-term basis. A dose-response relationship between ergot alkaloid concentration and hemodynamic changes in caudal (coccygeal), median sacral, and internal iliac arteries was hypothesized. Beef cows were randomly allocated to: Control (<15 g total ergot alkaloids/kg dry matter), Low (132 g/kg), Medium (529 g/kg), and High (2115 g/kg) groups (n=4 per group). Animals were fed 8.8 kg of dry matter daily for 4 days (pre-treatment), 7 days (treatment), and 4 days (post-treatment). The caudal, median sacral, and internal iliac arteries were examined daily using ultrasonography in B-mode and Doppler (colour and spectral) mode and hemodynamics endpoints were analyzed by repeated measures mixed model analyses. Caudal artery diameter decreased in the Medium (p=0.004) and High (p<0.001) groups compared to pre-treatment values and the pulsatility index increased (P≤0.033) in all ergot treatments during the post-exposure period compared to the Control group. Blood volume per pulse (mL) and blood flow (mL/min) through the caudal artery during the treatment period were reduced in the Medium (-1.0 mL reduction; p≤0.004) and High (-1.1 mL p≤0.006) groups compared to pre-treatment values. The median sacral artery diameter decreased in the Medium (p=0.006) and High (p=0.017) treatments compared to the Control group. No differences were detected in any hemodynamic endpoints for the internal iliac artery except changes in pulse rate (p=0.011). There was no treatment (p>0.554) or Treatment*Time interaction (p>0.471) for plasma prolactin concentration or body temperature. In conclusion, alterations in caudal artery hemodynamics were detected when cows were fed 529 and 2115g ergot alkaloids per kg dry matter per day for one week. The caudal artery was more sensitive to ergot alkaloids than the median sacral and internal iliac arteries. Our results partially support the hypothesis of a dose-response effect of ergot alkaloids in feed on hemodynamics.